L’imitazione come strumento per sapere e comunicare: un dialogo tra psicologia e scuola - Toselli, Monica; Cambi, Alessandro (Studi sulla Formazione/Open Journal of Education, 2019)
The binomy between psychology and school brings to mind, almost immediately, at least three different inflections on how these two terms might be linked to each other. The first, and most immediate, is the close relationship between psychologic research and test subjects availability, offered spontaneously by the scholastic institutions. The second one, refers to the contribution that the dialogue between pedagogy and psychology can offer to the formations of teachers, of any order, and their operativity, to be applied in regards of their students. And finally a fruitful dialogue implies that the school is able to offer interrogatives, themes for analysis and support in regards to the new issues that the same school needs to face. In light of this "dialogue", in this article the authors aim to present some ideas concerning the recent mechanisms of learning that might be transmitted to teachers during their formation and inspire them during their daily pedagogic action.